2013
DOI: 10.1373/clinchem.2013.209114
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of LC-MS for Therapeutic Drug Monitoring of Tacrolimus

Abstract: BACKGROUND: LC-MS is increasingly used for therapeutic drug monitoring of tacrolimus. A recent summary from an international proficiency-testing scheme demonstrated that the mass spectrometry respondents were the largest method group. However, these methods lack standardization, which may explain the relatively poor interlaboratory agreement for such methods. This study aimed to provide one path toward the standardization of tacrolimus quantification by use of LC-MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…For the results reported during the time period November 2012 and February 2014 (Figure 2), an average coefficient of variation (CV%) of 14.8% (range 6.5 – 23.2%) for LC-MS and 11.1% (4.2 – 26.4%) for QMS assays was observed. This is in the same range as observed for LC-MS/MS and immunoassays for other immunosuppressants such as tacrolimus 20 , including a higher inter-laboratory variability among TDM laboratories using LC-MS/MS in comparison to those using immunoassays 20,21 . It has been discussed that this may be due to the fact that immunoassays are highly automated and standardized, while LC-MS/MS assays are in most cases laboratory-developed and often use calibrators that are prepared in-house.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…For the results reported during the time period November 2012 and February 2014 (Figure 2), an average coefficient of variation (CV%) of 14.8% (range 6.5 – 23.2%) for LC-MS and 11.1% (4.2 – 26.4%) for QMS assays was observed. This is in the same range as observed for LC-MS/MS and immunoassays for other immunosuppressants such as tacrolimus 20 , including a higher inter-laboratory variability among TDM laboratories using LC-MS/MS in comparison to those using immunoassays 20,21 . It has been discussed that this may be due to the fact that immunoassays are highly automated and standardized, while LC-MS/MS assays are in most cases laboratory-developed and often use calibrators that are prepared in-house.…”
Section: Discussionsupporting
confidence: 69%
“…It has been discussed that this may be due to the fact that immunoassays are highly automated and standardized, while LC-MS/MS assays are in most cases laboratory-developed and often use calibrators that are prepared in-house. However, standardization of the calibrators has not always remedied the accuracy and inter-laboratory variability of LC-MS/MS assays 21,22 . There is evidence that in addition differences in sample preparation and vulnerability of electrospray ionization to matrix effects may play a role 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The largest mean difference from the reference measurement (exact matching-isotope dilution MS) was 4.4% [52]. A unified method by Thermo Fisher's Prelude online extraction and LC system coupled to a TSQ Vantage MS platform was evaluated for measuring cyclosporine A, tacrolimus, and sirolimus by 3 hospital labs [53].…”
Section: Commercialization and Standardization Of Lc-ms/ms Methodsmentioning
confidence: 99%
“…Lastly, a fourth group found that differences in hematocrit (20% to 45%), spotted blood volume (25,35,50,75, and 100 μL), and punch location did not affect immunosuppressant quantitation [39]. [46,47] Online solid phase extraction (analytical run time of 1 min) [48] No LC separation (analytical run time of 13 s) [49] Liquid handler [50] Commercialization/ Standardization 7-Lab tacrolimus unification [52] 3-Lab cyclosporine A, tacrolimus, and sirolimus unification [53] Much of these DBS validation studies involve the deposition of venous blood from a collection tube onto the paper. Two recent studies evaluated capillary blood from a finger stick.…”
Section: Non-traditional Sample Types For Lc-ms/ms Analysismentioning
confidence: 99%
“…Therefore some analytical procedures seek to analyze the four drugs simultaneously. This is currently achieved by high performance liquid chromatography (HPLC) coupled with a tandem mass spectrometer detector (MS/MS) [7][8][9][10][11]. To quantify drug concentrations different internal standards (ISs) are used.…”
Section: Introductionmentioning
confidence: 99%